Effects of midwife-led maternity services on postpartum wellbeing and clinical outcomes in primiparous women under China's one-child policy - Jing Hua; Liping Zhu; Li Du; Yu Li; Zhuochun Wu; Da Wo; Wenchong Du (BMC, 2018)
Abstract Background The Midwife-led maternity services have been implemented in China in response to the high rates of primiparous women and Caesarean Sections (CS) which may be related to China's one-child policy. However, few studies in China have been reported on the effectiveness of Midwife-led Care at Delivery (MCD) and the Continuity of Midwife-led Care (CMC) on postpartum wellbeing and other clinical outcomes. Therefore, evidence-based clinical validation is needed to develop an optimal maternity service for childbearing women in China. Methods A concurrent cohort study design was conducted with 1730 pregnant women recruited from 9 hospitals in Shanghai. Among the 1730 participants at baseline, 1568 participants completed the follow-up questionnaire, with a follow-up rate of 90.6%. Results Compared with the routine Obstetrician-led Maternity Care (OMC), Midwife-led Care at Delivery (MCD) was associated with CS rate (OR were 0.16; 95%CI: 0.11 to 0.25) and a higher total score of postpartum wellbeing (βwere 2.70; 95%CI: 0.70 to 4.70) when adjusting for the baseline differences and other confounders during delivery or postpartum period. Moreover, continuity of Midwife-led Care (CMC) was associated with CS rate (OR were 0.30; 95%CI: 0.23 to 0.41), as well as increased rate of breastfeeding within the first 24 h (OR were 2.49; 95% CI: 1.47 to 4.23), higher postpartum satisfaction (β = 4.52; 95% CI: 1.60 to 12.68), lower anxiety (βwere 0.66; 95% CI: 0.16 to 1.17), increased self-control (βwere 0.39; 95% CI: 0.02 to 0.76) and a higher total score of postpartum wellbeing (βwere 3.14; 95% CI: 1.54 to 4.75). Conclusion CMC is the optimal service for low-risk primiparous women under China's one-child policy, and is worthwhile for a general implementation across China.